Geographical and temporal variability in the extraction efficiency of bioactive metabolites from Cosmos bipinnatus - Mario Alberto Mora Ahuayo; María Dolores Mariezcurrena Berasain; Raúl Alberto Morales Luckie; Diego Girón Orozco (Applied Food Research, 2025)
Ruderal plants constitute a promising source of bioactive compounds with nutraceutical and therapeutic potential. In this study, we evaluated the influence of extraction method, geographic origin, and temporal factors on the chemical profile of Cosmos bipinnatus flowers collected from three high valley regions of the State of Mexico. Both aqueous and 50 % ethanolic extracts were analyzed for total phenols (TP), total saponins (TS), antioxidant capacity, pH, and color attributes. The 50 % ethanolic extraction consistently yielded higher amounts of bioactive compounds, with the extract from Zinacantepec exhibiting a TP of 80.31 ± 8.71 mg GA/g DW, TS of 113.49 ± 6.33 mg/g, and an antioxidant capacity (IC50) of 4.37 mg/mL. Additionally, temporal analysis revealed that TP increased significantly from 45.69 mg GA/g in 2019 to 85.72 mg GA/g in 2020, while 12 months of storage produced a moderate decline (from 48.09 to 45.69 mg GA/g). Principal component analysis further indicated that TP, pH, and color attributes accounted for over 70 % of the observed variability, highlighting the substantial impact of environmental conditions—particularly altitude—and seasonal factors on extract composition. These findings underscore the importance of optimizing extraction protocols and considering both geographic and temporal influences when harnessing the nutraceutical potential of Cosmos bipinnatus.